2020
DOI: 10.1080/16000870.2020.1718937
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the relationship between drought occurrences and their causal factors in Tigray Region, Northern Ethiopia

Abstract: Drought is controlled and enhanced by changes in the local and global climate factors. The changes in the global factors mainly occur on the vast oceanic surfaces, while the changes in the local factors occur in the area of drought influence. In order to skilfully forecast and monitor drought occurrences, it is crucial that the specific causal factors be identified and their links studied. Based on this concept, this study tried to establish a relationship between the drought occurrences in Tigray region and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 88 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…SST is a key climate variable that defines the interaction among oceanic and atmospheric phenomena (Wmo, n.d;Bojinski et al 2014), and SST variations had triggered many drought events worldwide (Fan et al 2017;Tefera et al 2020). The OND SST anomalies (Figure 7) showed increasing trend and a warm pool in the Arabian Sea and Bay of Bengal which proposes development of convection in Arabian Sea that might be a reason of precipitation deficit which consequently cause severe droughts in the Indian subcontinent (Preethi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SST is a key climate variable that defines the interaction among oceanic and atmospheric phenomena (Wmo, n.d;Bojinski et al 2014), and SST variations had triggered many drought events worldwide (Fan et al 2017;Tefera et al 2020). The OND SST anomalies (Figure 7) showed increasing trend and a warm pool in the Arabian Sea and Bay of Bengal which proposes development of convection in Arabian Sea that might be a reason of precipitation deficit which consequently cause severe droughts in the Indian subcontinent (Preethi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…SST is one of the most important oceanic climate variables that can be employed to interpret the interaction among various oceanic and atmospheric phenomena (Wmo, n.d;Bojinski et al 2014;Reynolds et al 2007). Various studies have reported that variations in SST have triggered drought events in different parts of the World (Fan et al 2017;Rajagopalan et al 2000;Lu and Delworth 2005;Feng et al 2008;Annamalai et al 2013;Tefera et al 2020).…”
Section: Sea Surface Temperature (Sst)mentioning
confidence: 99%
“…The global SST is among the key factor that plays a significant role in determining the variability of the monthly, annual and decadal precipitation patterns. Alhamshry Previous studies confirm that the spatial and temporal variability in the precipitation of Ethiopia is attributed to the variations in SSTs over the Atlantic, Indian, and Pacific Oceanic indices (Degefu et al, 2017;Zeleke et al, 2017;Dubache et al, 2019;Alhamshry et al, 2020;Molla, 2020;Tefera et al, 2020;& Bayable et al, 2021).…”
Section: Resultsmentioning
confidence: 92%
“…Besides, the drying trend in the southern and northern of Ethiopia is associated with Atlantic drought influencing factor in Ethiopia (Tefera et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation